Pemanfaatan layanan cloud computing dan docker container untuk meningkatkan kinerja aplikasi web - Ekaputra, Achsan Rizky; Affandi, Arif Saivul (Universitas Merdeka Malang, 2023)
This research aims to analyze and implement the utilization of Content Delivery Networks (CDN) and cloud computing services in web applications using Nginx Proxy Manager and Docker containers. This research uses experimental methods and case studies to analyze the performance of web applications before and after using CDN services and implementing the application in a cloud computing environment using Docker containers. Next, Nginx Proxy Manager is used to provide a user-friendly interface for configuring and managing Nginx proxy servers. Docker containers are used to manage web applications and proxy servers. Â In the CDN and cloud computing environment, Cloudflare & Google Cloud Platform will be used as service providers. The results of this research indicate a significant improvement in the security and reliability of web applications after implementing CDN services and adopting a cloud computing environment. Additionally, this research provides insight into how to use Nginx Proxy Manager and Docker container to manage web applications efficiently and effectively in a cloud computing environment.